2021
DOI: 10.1186/s40798-021-00338-2
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Strength Database for Muscle Maximal Voluntary Endurance Field Tests: Normative Data

Abstract: Background Different field tests are used to evaluate muscle capacity, in particular maximal voluntary isometric endurance. However, although there are some normative values for a few muscle endurance tests, these do not consider the weight, height, gender, or age of individuals, which are well-known factors that influence muscle performance. Hypothesis/Purpose The purpose of this study was to investigate the test–retest reproducibility of eight fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
4
1
Order By: Relevance
“…The post-treatment medians in this study are mostly consistent with those reported in the literature [41][42][43][44][45][46]. For TE, a cross-sectional study of 9413 Danish school students (mean age of 17 years, SD = 0.6) was 147.9 s (SD = 57.3) for males and 148.9 s (SD = 66.9) for females [47].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The post-treatment medians in this study are mostly consistent with those reported in the literature [41][42][43][44][45][46]. For TE, a cross-sectional study of 9413 Danish school students (mean age of 17 years, SD = 0.6) was 147.9 s (SD = 57.3) for males and 148.9 s (SD = 66.9) for females [47].…”
Section: Discussionsupporting
confidence: 88%
“…More recently, norms for TE were reported as a mean of 181.0 s (±66.8) for males and a mean of 183.2 s (±92.8) for females, which are longer than those seen in the TE baseline times in our study [42]. However, these means were established from 20 volunteers aged 40.9 ± 11.6 years old, ranging in age from 21 to 58 years, who had no history of acute or chronic back disease, and therefore were not representative of our study sample [42].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Given that people with PFP can be divided into different subgroups, depending on the individual aetiologies [15], it is important to determine whether quadriceps weakness is part of the cause for PFP in the individual, and to track whether progress is made when conducting an exercise program to improve quadriceps strength [15]. Presently, the ‘gold standard’ instrument for the evaluation of quadriceps strength is the isokinetic dynamometer (ID) [16,17], which is beyond the affordability of most clinicians (∼R500k-R1.50mil). Although a more reasonable alternative to the ID exists, such as a handheld dynamometer (HHD) [17], the reliability of an HHD depends on the strength and aptitude of the practitioner [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is also essential to track whether progress is made when conducting an exercise program to improve quadriceps strength such that more sound and robust clinical decisions can be made [ 15 ]. Presently, the ‘gold standard’ instrument for the evaluation of quadriceps strength is the isokinetic dynamometer (ID) [ 16 , 17 ], which is beyond the affordability of most clinicians. Although more reasonable alternatives to the ID exists, such as a handheld dynamometer (HHD) [ 17 ], the reliability of an HHD depends on the strength and aptitude of the practitioner [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%